2020
DOI: 10.3390/v12010109
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Hepatitis E Vaccines: Antigenic Analysis and Serological Evaluation

Abstract: Hepatitis E virus (HEV) infection causes sporadic outbreaks of acute hepatitis worldwide. HEV was previously considered to be restricted to resource-limited countries with poor sanitary conditions, but increasing evidence implies that HEV is also a public health problem in developed countries and regions. Fortunately, several vaccine candidates based on virus-like particles (VLPs) have progressed into the clinical development stage, and one of them has been approved in China. This review provides an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 75 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…4 b). It has been observed that 54 kDa protein can form virus-like particles that enhances their immunogenic potential (Chattopadhyay et al 2017 , Gupta et al 2020 , Li et al 2020 ). The antibody response is dependent on the neutralization epitopes located at C-terminus of ORF2 (E2, 459-606aa) and bigger protein HEV239 (298-606aa) also contains an additional neutralization epitope (Zhao et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 b). It has been observed that 54 kDa protein can form virus-like particles that enhances their immunogenic potential (Chattopadhyay et al 2017 , Gupta et al 2020 , Li et al 2020 ). The antibody response is dependent on the neutralization epitopes located at C-terminus of ORF2 (E2, 459-606aa) and bigger protein HEV239 (298-606aa) also contains an additional neutralization epitope (Zhao et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, prophylactic vaccination could potentially be an effective method to protect people from HEV infection. Several vaccine candidates based on virus-like particles (VLPs) have progressed into the clinical development stage, and one of them currently approved in China, with evidence on safety and efficacy including in pregnant women [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The commercial Hecolin HEV vaccine, based on a recombinant E. coli -expressed capsid protein p239, has demonstrated its safety and efficacy in a large-scale phase III clinical trial [70] and is approved and licensed for use in China in 2012 [71] . Furthermore, the Hecolin vaccine is currently undergoing a phase IV clinical trial to assess the safety, immunogenicity, and effectiveness in pregnant women in rural areas of Bangladesh [72] .…”
Section: Viral Proteins Their Primary Structural Features and Functionsmentioning
confidence: 99%